The influence of peer accountability on attention during gameplay - Zhang, Yaqian (2019)
The comparative advantages of competitive and cooperative multiplayer gameplay designs have been studied with mixed results. In this study, we have attempted to minimize other cooperative design attributes in order to focus on evaluating the effects of strong peer accountability on players' overall and sustained attention levels during competition and cooperation. A novel multiplayer game based on a cognitive task that uses the Stroop effect was developed and deployed in trials where quantitative in-game data measuring players' error rates and reaction times were collected for comparative analysis. The results show that players demonstrate higher levels of attention when they were made accountable to their partners as they make significantly less errors when cooperating than when competing. In addition, the individual response time data gathered reveals that peer accountability has a more positive influence on the performance of the slower partner and this performance improvement was not sustainable under situation where large performance disparity existed within the team. Physical proximity however, was not observed to have any significant positive influence on players’ performance during cooperative gameplay.